Rancang Bangun Aplikasi Edukasi Hardware Komputer Berbasis Teknologi Augmented Reality dengan Menggunakan Android - Andri Wahyu Saputra; adhi susano; Puji Astuti (Faktor Exacta, 2018)
In studying and visualizing computer devices students and students tend to experience difficulties when they want to learn and memorize computer units. This study aims to create a learning application about computer hardware by utilizing the development of Android-based smartphone technology using augmented reality technology. The development method used to build this application is the waterfall method. Making this application uses C # language and unity 3D game engine software. This application applies vuforia as SDK to create an augmented reality that runs on the Android OS and uses a virtual button located in the marker. This application provides information and displays 3D objects about computer hardware, specifically for processing units, namely processor, motherboard, RAM, hard drive and VGA. The chosen research subjects were students and students who had studied computer hardware components. This is determined to find out the difficulties faced by students and students in studying the material of computer hardware. The purpose of making this application is that students, students or even people outside the IT profession can study computer hardware material with the help of applications that provide 3D object models and relevant information without having to look at books or other media. Key Word : Android, Augmented Reality, Computer, Waterfall, Unity